Hubungan antara stigma terhadap anak yatim AIDS, tekanan persekitaran dan pengurusan penjagaan kanak-kanak HIV/AIDS di institusi perlindungan kanak-kanak: satu kajian awal - Ezarina Zakaria; Nur Saadah Mohamad Aun; Wan Nornazmiera Wan Hamat (Penerbit Universiti Kebangsaan Malaysia, 2018)
The management of child care cases toward children with HIV/AIDS in institution are still receiving less attention whereas day after day, there has been an increase in the number of shelters existed for children. This article discusses the initial findings of the study which aimed to identify the relationship between the stigma towards orphans with AIDS and environmental stress within the institution and the management of HIV/AIDS child care case. A total of 140 caretakers in 7 child protection institutions were selected through purposive sampling. Data were collected using a feedback form. Measurement tools used were from Hennepin County Case Management Survey, Manual Measuring HIV Stigma and Discrimination Among Health Facility Staff Questionnaire and HSE Management Standards Indicator Tools. Data analysis found that a total of 98.6% respondents showed a higher level of case management, 80.7% respondent had a moderate level of stigma and a total of 83.6% showed average level of environmental stress. Pearson Correlation analysis showed that there were: i) significant relationship between environmental stress with case management, r(140) = .193, p<0.05; ii) significant negative relationship between stigma and case management, r(140) = -0.261, p<0.05; and iii) significant relationship between stigma towards children with AIDS with environmental stress among their caretakers, r(140) = .0732, p<0.01. Besides that, results showed that 76% respondents never received special training in managing HIV/AIDS children. Therefore, it is recommended that every HIV/AIDS child protection institute needs to prepare a regular training. Caretakers should be provided with shelter management courses that provide various background of HIV/AIDS children’s case, a need towards handling children with HIV/AIDS specifically, skills in handling stigma towards HIV and training on how to manage institutional environmental stress.